Drug-Related Problems Leading to Hospitalization: A Literature Review - Annisa Nur Kharisma; Fita Rahmawati; Soni Siswanto (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2026)
Background: Drug-related problems (DRPs) are described as problems associated with medications that can lead to treatment failure and may also cause hospital admissions. The novelty of this study is that it supplements previous research data with the latest data on DRPs leading to hospital stays, specifically articles published between 2021 and 2025. Objective: This study aims to identify the prevalence of hospitalization due to DRPs, the types of DRPs that lead to hospital admissions, the medications involved, and the risk factors for DRPs. Methods: A literature search was conducted across the PubMed, ScienceDirect, and Scopus databases, limiting publication years to 2021-2025. Results: In the 12 studies reviewed, the frequency of hospitalization due to DRP varied between 5,0% to 57,9%. Adverse drug reactions (ADRs), non-compliance, drug interactions, dosing errors, and incomplete therapy indication were the most common types of DRPs that lead to hospitalization. The drugs most commonly involved in DRPs were antidiabetic agents, cardiovascular agents, diuretics, and antineoplastic agents. Age, polypharmacy, and the number and severity of comorbidities were identified as primary risk factors for hospitalization caused by DRPs. Conclusion: The frequency of hospitalization due to DRP varied between 5,0% to 57,9%. Factors such as age, number of medications, and comorbidities influence the frequency of DRPs.